Evaluating Ecodesign Methodology in Yacht Design: A Professional Workshop Case Study - Ruggiero, Ludovico; Piccioni, Massimo; Ratti, Andrea (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The yachting industry faces increasing pressure to adopt sustainable practices driven by regulatory requirements and evolving consumer expectations. This study explores the application of Life Cycle Design (LCD), also referred to as ecodesign, methodologies within yacht design to address environmental challenges. Despite the critical importance of early-stage design in determining a product's environmental impact, the yacht sector lacks industry-specific sustainability guidelines.This research investigated the practical implementation of a generic LCD methodology - specifically the MPDS (Method for Product Design for Environmental Sustainability) - through an intensive workshop involving young professional yacht designers. Participants were tasked with developing concept designs for a 50-foot charter yacht, applying six LCD strategies: use extension, material consumption reduction, energy consumption reduction, material life extension, toxicity reduction, and resources conservation.The study outlined both opportunities and limitations in applying MPDS to yacht design. While participants achieved incremental improvements in certain strategies, the research highlighted the need for context-specific adaptations. Challenges included the methodology's generic nature and the complexity of yacht design processes.The findings underscore the potential of LCD principles in promoting sustainability within the nautical industry and provide a foundation for developing tailored guidelines that can effectively integrate environmental considerations into yacht design processes.